Improving assessment processes in higher education: Student and teacher perceptions of the effectiveness of a rubric embedded in a LMS - Atkinson, Doug; Lim, S. (ASCILITE, 2013)
Students and teachers play different roles and thus have different perceptions about the effectiveness of assessment including structure, feedback, consistency, fairness and efficiency. In an undergraduate Business Information Systems course, a rubric was designed and semi-automated through a learning management system (LMS) to provide formative feedback. Action research with a qualitative approach was undertaken by the teacher. A questionnaire was administered to the 55 students to gather their perceptions of the effectiveness of the process. Students reported benefits of clearly being able to see what they needed to do, what they had achieved, and what they needed to do to improve. The majority (95%) recommended further use of the rubric process. From the teacher's perspective, a key benefit was an estimated 40% reduction in marking time and improved student satisfaction with feedback. An insight from the student feedback and teacher reflection was that there is a balance between providing clear detailed structure versus challenging students with freedom to deal with the ambiguity of open ended issues. The study provides practical insights for further roll-out of assurance of learning initiatives based on rubrics embedded in LMSs, and contributes a model for further research into student and teacher perceptions of assessment effectiveness. Australasian Journal of Educational Technology © 2013.